A Preview of the Mobile Marketing Research - Paraschiv, Daniel Claudiu (International Journal of Economic Practices and Theories, 2014)
The purpose of this paper is to have general overview over the mobile industry from the marketing research point of view. This paper aims to highlight the importance of the mobile marketing research and to understand the evolution trend of mobile technology for future marketing research projects. The potential of the mobile technology is making mobile marketing research win more terrain in the detriment of the classic, but still intensively used, marketing research tools. The preview is based on the few papers which are approaching this new but fast growing niche. There is the need of having a general guideline for the mobile marketing research but the existing literature is falling short on creating the framework for the mobile marketing research. There are few papers which are approaching this area of interest, creating an inconsistent and a fragmented description of probably the main direction of the marketing research development.